Structures and Mechanical Properties of Some Dual-Phase Steels with Low Manganese Content - Constantin Dulucheanu; Traian Lucian Severin; Delia Aurora Cerlinca; Luminita Irimescu (Metals, 2022)
In recent years, to reduce cars costs, research has been conducted on dual-phase steels with low manganese content (below 1.0%). This study investigated the influence of technological parameters of heat treatment (heating temperature and cooling medium) on such steels’ structures and mechanical properties. The ferrite-martensitic structures, specific for dual-phase steels, were obtained by intercritical quenching: heating of samples (made of alloys with 0.511% Mn, respectively 0.529% Mn) to temperatures located between critical points Ac1 and Ac3, followed by cooling in water without mechanical agitation and in water activated with ultrasounds at the frequency of 59 kHz. Through metallographic analyses and tensile tests, it was possible to determine the volume fraction of martensite, the ferrite microhardness, the ultimate tensile strength, the total elongation, and with the obtained data, their variations with the heating temperature and the cooling medium were established. Raising the heating temperature (between 760 °C and 820 °C) and using ultrasounds at cooling increased the volume fraction of martensite and the ferrite microhardness. This fact has increased the mechanical strength and reduced the deformability of the studied dual-phase steels. Intercritical quenching in water activated with ultrasounds provided values of structural characteristics and mechanical properties very close to those obtained by quenching in water without mechanical agitation, but was accomplished using a higher-temperature heating. The results obtained were compared with those determined in previous research, performed on dual-phase steel with 1.90% Mn.